B–N/B–H Transborylation: borane-catalysed nitrile hydroboration - Meger, Filip; Kwok, Alexander C. W.; Gilch, Franziska; Willcox, Dominic R.; Hendy, Alex J.; Nicholson, Kieran; Bage, Andrew D.; Langer, Thomas; Hunt, Thomas A.; Thomas, Stephen P. (Beilstein Journal of Organic Chemistry, 2022)
The reduction of nitriles to primary amines is a useful transformation in organic synthesis, however, it often relies upon stoichiometric reagents or transition-metal catalysis. Herein, a borane-catalysed hydroboration of nitriles to give primary amines is reported. Good yields (48–95%) and chemoselectivity (e.g., ester, nitro, sulfone) were observed. DFT calculations and mechanistic studies support the proposal of a double B–N/B–H transborylation mechanism.
Keywords: boron; catalysis; hydroboration; nitrile; transborylation

Ullmann's Encyclopedia of Industrial Chemistry - Herzog, B. D.; Smiley, R. A. (Hexamethylenediamine, 2012)

(untitled) - Roughley, S. D.; Jordan, A. M. (J. Med. Chem., 2011)

(untitled) - Askew, S. D.; McNulty, B. M. S. (Weed Technol., 2014)

(untitled) - Brown, H. C.; Krishnamurthy, S. (Tetrahedron, 1979)

(untitled) - Feller, M. (Phys. Sci. Rev., 2019)

(untitled) - Lu, Q.; Liu, J.; Ma, L. (J. Catal., 2021)

(untitled) - Hayrapetyan, D.; Khalimon, A. Y. (Chem. – Asian J., 2020)

(untitled) - Rezaei Bazkiaei, A.; Findlater, M.; Gorden, A. E. V. (Org. Biomol. Chem., 2022)

(untitled) - Kuciński, K.; Hreczycho, G. (Green Chem., 2020)

(untitled) - Wilkins, L. C.; Melen, R. L. (Coord. Chem. Rev., 2016)

Handbook on the Toxicology of Metals - Nordberg, G. F.; Fowler, B. A.; Nordberg, M. (Toxicology of Metals: Overview, Definitions, Concepts, and Trends, 2015)

(untitled) - Egorova, K. S.; Ananikov, V. P. (Organometallics, 2017)

(untitled) - Weetman, C.; Anker, M. D.; Arrowsmith, M.; Hill, M. S.; Kociok-Köhn, G.; Liptrot, D. J.; Mahon, M. F. (Chem. Sci., 2016)

(untitled) - Mukherjee, D.; Shirase, S.; Spaniol, T. P.; Mashima, K.; Okuda, J. (Chem. Commun., 2016)

(untitled) - Bismuto, A.; Cowley, M. J.; Thomas, S. P. (ACS Catal., 2018)

(untitled) - Li, J.; Luo, M.; Sheng, X.; Hua, H.; Yao, W.; Pullarkat, S. A.; Xu, L.; Ma, M. (Org. Chem. Front., 2018)

(untitled) - Ding, Y.; Ma, X.; Liu, Y.; Liu, W.; Yang, Z.; Roesky, H. W. (Organometallics, 2019)

(untitled) - Liu, W.; Ding, Y.; Jin, D.; Shen, Q.; Yan, B.; Ma, X.; Yang, Z. (Green Chem., 2019)

(untitled) - Harinath, A.; Bhattacharjee, J.; Panda, T. K. (Adv. Synth. Catal., 2019)

(untitled) - Ghosh, P.; Jacobi von Wangelin, A. (Org. Chem. Front., 2020)

(untitled) - Sarkar, N.; Bera, S.; Nembenna, S. (J. Org. Chem., 2020)

(untitled) - Zhang, Z.; Huang, S.; Huang, L.; Xu, X.; Zhao, H.; Yan, X. (J. Org. Chem., 2020)

(untitled) - Gautam, N.; Logdi, R.; Sreejyothi, P.; Rajendran, N. M.; Tiwari, A. K.; Mandal, S. K. (Chem. Commun., 2022)

(untitled) - Bedi, D.; Brar, A.; Findlater, M. (Green Chem., 2020)

(untitled) - Yan, B.; He, X.; Ni, C.; Yang, Z.; Ma, X. (ChemCatChem, 2021)

(untitled) - He, X.; Yan, B.; Ni, C.; Zhao, Y.; Yang, Z.; Ma, X. (Asian J. Org. Chem., 2021)

(untitled) - Jeong, E.; Heo, J.; Park, S.; Chang, S. (Chem. – Eur. J., 2019)

(untitled) - Jayaraman, A.; Powell-Davies, H.; Fontaine, F.-G. (Tetrahedron, 2019)

(untitled) - Benn, K.; Nicholson, K.; Langer, T.; Thomas, S. P. (Chem. Commun., 2021)

(untitled) - Brown, H. C.; Krishnamurthy, S.; Yoon, N. M. (J. Org. Chem., 1976)

(untitled) - Adams, R. M.; Braun, L. M.; Braun, R. A.; Crissman, H. R.; Opperman, M. (J. Org. Chem., 1971)

Green chemistry: Theory and Practice - Anastas, P. T.; Warner, J. C. (Oxford University Press, 2000)

(untitled) - Gudun, K. A.; Slamova, A.; Hayrapetyan, D.; Khalimon, A. Y. (Chem. – Eur. J., 2020)

(untitled) - Kitano, T.; Komuro, T.; Tobita, H. (Organometallics, 2019)

(untitled) - Ghosh, C.; Kim, S.; Mena, M. R.; Kim, J.-H.; Pal, R.; Rock, C. L.; Groy, T. L.; Baik, M.-H.; Trovitch, R. J. (J. Am. Chem. Soc., 2019)

(untitled) - Pandey, V. K.; Tiwari, C. S.; Rit, A. (Org. Lett., 2021)

(untitled) - Pawar, G. G.; Robert, F.; Grau, E.; Cramail, H.; Landais, Y. (Chem. Commun., 2018)

(untitled) - Romero, E. A.; Peltier, J. L.; Jazzar, R.; Bertrand, G. (Chem. Commun., 2016)

(untitled) - Wang, Z.; Wang, Y.; Pasangulapati, J. P.; Stover, K. R.; Liu, X.; Schier, S.; Weaver, D. F. (Eur. J. Med. Chem., 2021)

(untitled) - Zhao, Y.; Truhlar, D. G. (Theor. Chem. Acc., 2008)

(untitled) - Zou, W.; Gao, L.; Cao, J.; Li, Z.; Li, G.; Wang, G.; Li, S. (Chem. – Eur. J., 2022)

(untitled) - Yalpani, M.; Köster, R.; Boese, R. (Chem. Ber., 1993)